Dynamic modelling provides new insights into development and maintenance of Lake Kivu's density stratification. (January 2022) - Bärenbold, Fabian; Kipfer, Rolf; Schmid, Martin
Abstract: Lake Kivu is a 485 m deep, Central-East African rift lake with huge amounts of carbon dioxide and methane dissolved in its stably stratified deep waters. In view of future large-scale methane extraction, one-dimensional numerical modelling is an important and computationally inexpensive tool to analyze the evolution of stratification and the content of gases in Lake Kivu. For this purpose, we coupled the physical lake model Simstrat to the biogeochemical library AED2. Compared to an earlier modelling approach, this coupled approach offers several key improvements, most importantly the dynamic evaluation of mixing processes over the whole water column, including a parameterization for double-diffusive transport, and the density-dependent stratification of groundwater inflows. The coupled model successfully reproduces today's near steady-state of Lake Kivu, and we demonstrate that a complete mixing event ∼2000 years ago is compatible with today's physical and biogeochemical state. Highlights: The physical lake model Simstrat is coupled to the biogeochemical library AED2. Modelling confirms that Lake Kivu's stratification is driven by groundwater springs. The evolution of Lake Kivu from completely mixed to today's state takes ∼2000 years. Elevated 3 H values in the deep water suggest that part of the groundwater is modern.